Diffraction efficiency of H-PDLC film with comb-shaped electrodes - Kubytskyi, V.; Reshetnyak, V.; Galstian, T. (Functional Materials, 2006)
А theoretical model of holographic polymer-dispersed liquid crystal film with comb-shaped
electrodes has been constructed. The model combines anisotropic coupled-wave theory, Monte-Carlo simulations for director profile within a liquid crystal droplet and statistical averaging with the orientational distribution function for droplet symmetry axes. Influence of the electric field applied along the grating vector on the diffraction efficiency has been studied. The results obtained indicate a way to improve the grating characteristics. Построена теоретическая модель голографической полимер-диспергированной жидкокристаллической (Г-ПДЖК) пленки с гребенчатыми электродами. В модели объединяется анизотропная теория связанных волн, компьютерное моделирование распределения директора внутри жидкокристаллической капли методом Mонте-Карло и статистическое усреднение с функцией распределения осей капель. Исследовано влияние электрического поля, приложенного вдоль вектора решетки, на дифракционную эффективность. Полученные результаты указывают способ улучшения характеристик решетки. Побудовано теоретичну модель голографiчної полiмер-диспергованої рiдкокристалiчної (Г-ПДРК) плiвки з гребiнчастими електродами. У моделi поєднується анiзотропна теорiя зв'язаних хвиль, комп'ютерне моделювання розподiлу директора всерединi рiдкокристалiчної краплi методом Mонте-Карло та статистичне усереднення з функцiєю розподiлу вiсей симетрiї крапель. Дослiджено вплив електричного поля, прикладеного вздовж вектора гратки, на дифракцiйну ефективнiсть. Отриманi результати вказують шлях покращення характеристик гратки.